Cerebrospinal fluid biomarkers of central catecholamine deficiency in Parkinson’s disease and other synucleinopathies - Goldstein, David S.; Holmes, Courtney; Sharabi, Yehonatan (Brain (London, England : 1878), 2012)
Central catecholamine deficiency characterizes α-synucleinopathies such as Parkinson's disease. We hypothesized that cerebrospinal fluid levels of neuronal metabolites of catecholamines provide neurochemical biomarkers of these disorders. To test this hypothesis we measured cerebrospinal fluid levels of catechols including dopamine, norepinephrine and their main respective neuronal metabolites dihydroxyphenylacetic acid and dihydroxyphenylglycol in Parkinson's disease and two other synucleinopathies, multiple system atrophy and pure autonomic failure. Cerebrospinal fluid catechols were assayed in 146 subjects-108 synucleinopathy patients (34 Parkinson's disease, 54 multiple system atrophy, 20 pure autonomic failure) and 38 controls. In 14 patients cerebrospinal fluid was obtained before or within 2 years after the onset of parkinsonism. The Parkinson's disease, multiple system atrophy and pure autonomic failure groups all had lower cerebrospinal fluid dihydroxyphenylacetic acid [0.86 ± 0.09 (SEM), 1.00 ± 0.09, 1.32 ± 0.12 nmol/l] than controls (2.15 ± 0.18 nmol/l; P < 0.0001; P < 0.0001; P = 0.0002). Dihydroxyphenylglycol was also lower in the three synucleinopathies (8.82 ± 0.44, 7.75 ± 0.42, 5.82 ± 0.65 nmol/l) than controls (11.0 ± 0.62 nmol/l; P = 0.009, P < 0.0001, P < 0.0001). Dihydroxyphenylacetic acid was lower and dihydroxyphenylglycol higher in Parkinson's disease than in pure autonomic failure. Dihydroxyphenylacetic acid was 100% sensitive at 89% specificity in separating patients with recent onset of parkinsonism from controls but was of no value in differentiating Parkinson's disease from multiple system atrophy. Synucleinopathies feature cerebrospinal fluid neurochemical evidence for central dopamine and norepinephrine deficiency. Parkinson's disease and pure autonomic failure involve differential dopaminergic versus noradrenergic lesions. Cerebrospinal fluid dihydroxyphenylacetic acid seems to provide a sensitive means to identify even early Parkinson's disease.